2010
DOI: 10.1089/ten.tea.2010.0045
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected Macroporous Poly(Ethylene Glycol) Cryogels as a Cell Scaffold for Cartilage Tissue Engineering

Abstract: Macroporous networks of poly(ethylene glycol) (PEG) with interconnected pores can be created by cryogelation techniques. In this study, we describe the potential application of such PEG cryogels as scaffolds for cartilage tissue engineering. Three-dimensional macroporous cryogels were evaluated for chondrocyte growth and production of cartilage-specific extracellular matrix (ECM). Seeded primary bovine chondrocytes showed homogeneous distribution throughout the cryogels. DNA content suggests continuous cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…30,34,35 However, these porous constructions of scaffolds cannot match the biological characteristics of cartilage. DC-ECM and other oriented scaffolds can facilitate the migration and expression of cells and strengthen the biomechanical properties of materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,34,35 However, these porous constructions of scaffolds cannot match the biological characteristics of cartilage. DC-ECM and other oriented scaffolds can facilitate the migration and expression of cells and strengthen the biomechanical properties of materials.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were deparaffinized, rehydrated and stained with hematoxylin and eosin (H&E; Sigma) to observe cells within the scaffolds, 30 then stained with toluidine blue and safranin O to evaluate GAG. Collagen type II content was detected by immunohistochemistry.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…4,5 In particular, the average pore size of a hydrogel can greatly affect cell infiltration, proliferation, and migration within the scaffold and different optimum pore sizes have been demonstrated for different tissue repair applications. 4,6,7 A number of fabrication techniques have been developed to generate pores within hydrogels for tissue engineering applications, including electrospinning, 8,9 gas foaming, [10][11][12][13] freeze-thaw, 14,15 phase separation, [16][17][18][19] and salt leaching. [20][21][22] However, the majority of these techniques for generating macroporous hydrogels often involve cytotoxic procedures or chemicals that undermine a key advantage hydrogels have over other traditional tissue engineering scaffolds: the ability to encapsulate viable cells with a homogeneous distribution within the 3D scaffold during fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that concentration more or less than the optimum concentrations lead to the formation of gels those lacked porous network, had less elasticity, were brittle and soft or weak in mechanical strength. Moreover, only PEG cryogels [43] and gelatin cryogels have already been synthesized. Our research group has also analyzed the cell proliferation on gelatin cryogels (unpublished data).…”
Section: Fabrication Of Peg-gelatin Cryogelsmentioning
confidence: 99%
“…It has been used as a scaffolding material as an adhesive and absorbent pad for wound dressing and also for surgical use [39][40][41]. Another polymer i.e., PEG acts as an ideal material for mimicking microenvironment or acting similar to ECM and also reduces inflammation after implantation due to its inert surface and has shown promising results in various bioengineering applications such as in drug delivery, neural, cartilage, liver and cardiac [42][43][44][45][46][47][48][49]. PEG has low protein adsorption ability and this property is not beneficial for cell adhesion whereas, gelatin helps in cell adherence.…”
Section: Introductionmentioning
confidence: 99%